2014
DOI: 10.1177/0888406414557677
|View full text |Cite
|
Sign up to set email alerts
|

Delving Deeper Into the Construct of Preservice Teacher Beliefs About Reading Instruction for Students With Disabilities

Abstract: The purpose of this study was to complete an in-depth examination of the construct of teacher beliefs by investigating preservice teachers’ beliefs about reading instruction for students with disabilities. Interview and artifact data were collected for 11 preservice teachers during a 10-month period. Dimensions of beliefs investigated were expressed beliefs and beliefs-in-use, the stability of beliefs, and sources of beliefs. Results indicate that preservice teachers’ beliefs systems are complex, made up of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
1
13
0
6
Order By: Relevance
“…One line of research in special education focuses on preservice teacher beliefs. Leko et al (2014) studied 11 preservice teachers’ beliefs over a 10-month period. They found that strong beliefs did not change during this period.…”
Section: How Do We Define Beliefs?mentioning
confidence: 99%
See 1 more Smart Citation
“…One line of research in special education focuses on preservice teacher beliefs. Leko et al (2014) studied 11 preservice teachers’ beliefs over a 10-month period. They found that strong beliefs did not change during this period.…”
Section: How Do We Define Beliefs?mentioning
confidence: 99%
“…Special education research has focused on the beliefs of special education teachers and general education teachers providing instruction to students with disabilities. The research on special education and general education teachers has examined preservice teacher beliefs (Beacham & Rouse, 2012; Leko, Kulkarni, Lin, & Smith, 2014; Sharma & Sokal, 2013), teacher efficacy (Allinder, 1995; Brady & Woolfson, 2008; Brownell & Pajares, 1999), beliefs about disabilities and instructional practices (Jordan, Schwartz, & McGhie-Richmond, 2009; Jordan & Stanovich, 2003), beliefs affecting literacy instruction (Berry, 2006; Hollenbeck, 2013; Ruppar, Gaffney, & Dymond, 2015), and how beliefs can change over time (Ruiz, Rueda, Figueroa, & Boothroyd, 1995). Yet, there is a dearth of research focusing on the potential impact of special education teachers’ beliefs about their roles and responsibilities and how that influences their instructional practices.…”
mentioning
confidence: 99%
“…Leko, Kalukarni, Lin, and Smith (2015) gathered data from 11 preservice special education teachers who were enrolled in a reading methods course. The researchers examined both expressed beliefs and what they called “beliefs-in-use,” or how beliefs might materialize through pedagogy.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, across the entire sample, the extent of reading difficulties in childhood was related to more positive teacher-efficacy, even after accounting for variance associated with gender and year of program. Preservice teachers who have struggled to acquire literacy skills may have more experience as recipients of varied instructional strategies in their own past (Leko, Kulkarni, Lin, & Smith, 2015). This increased familiarity may lend itself to feeling more confident with varied instructional approaches to meet the needs of all learners (see also, Csoli & Gallagher, 2012).…”
Section: Discussionmentioning
confidence: 99%